Efektivitas Edukasi DAGUSIBU (Dapatkan, Gunakan, Simpan, dan Buang) Obat sebagai Media Peningkatan Kesadaran Siswa SMK Muhammadiyah 1 Batu - Syifa’, Nailis; Azmi, Muhammad Rasyid; Khailillah, Adiqta Nasywa; Akbar, Gani Farros; Tamira, Nurjihan; Amaliya, Nasywa; C.S, M. Raditya Lingga; Putri, Indy Eka; Fadhil, Adelia; Dzaroini, Saada; Dewi, Diah Kumala (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This counseling aims to increase awareness and understanding of SMK Muhammadiyah 1 Batu students regarding the correct use of drugs through DAGUSIBU (Get, Use, Store, and Dispose) education. The lack of drug literacy among adolescents often leads to fatal errors, such as inappropriate use of over-the-counter drugs, wrong drug selection, dosage errors, and improper storage and disposal of drugs, which can have negative impacts on health and the environment. This activity is part of the Drug Awareness Family Movement (GKSO) program initiated by the Indonesian Pharmacists Association (IAI). The implementation method consists of several stages: (1) pre-test to measure students' initial knowledge; (2) education session involving material presentation through presentations, group discussions, and direct demonstrations on how to store and dispose of drugs properly; and (3) post-test to assess increased understanding after the intervention. The activity was carried out on May 26, 2025 with a total of 43 participants from class XI SMK Muhammadiyah 1 Batu. The pre-test results showed that 88.37% of students were in the understanding category, 9.30% were quite understanding, and 2.33% were less understanding. After the education session, the post-test results showed a significant increase: 94.12% of students were classified as understanding, and no students were in the less understanding category. This increase shows the effectiveness of the educational approach used in increasing drug literacy among students. It is hoped that students who have gained this understanding can become agents of change in disseminating correct information about drug management to families and communities in their surroundings.